2010
DOI: 10.2174/1875397301004010084
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase Reporter Assay System for Deciphering GPCR Pathways

Abstract: The G protein coupled receptors (GPCR) represent the target class for nearly half of the current therapeutic drugs and remain to be the focus of drug discovery efforts. The complexity of receptor signaling continues to evolve. It is now known that many GPCRs are coupled to multiple G-proteins, which lead to regulation of respective signaling pathways downstream. Deciphering this receptor coupling will aid our understanding of the GPCR function and ultimately developing drug candidates. Here, we report the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 16 publications
3
149
0
1
Order By: Relevance
“…In addition, we monitored apela induction of the phosphorylation of p42/44 ERKs, known to be downstream of Gi/Go signaling (23). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we monitored apela induction of the phosphorylation of p42/44 ERKs, known to be downstream of Gi/Go signaling (23). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in supplementary material Fig. S2, norrin is not capable of stimulating different G proteins (Gs, Gi, Gq and G12) mediated by LGR4, 5 or 6 (as determined by CRE-, SRE-, NFAT-and SRF-RE reporter assays) (Cheng et al, 2010). Because LGR4, 5 and 6 are known to mediate Wnt signaling (de Lau et al, 2011), we further tested the ability of norrin to activate Wnt signaling mediated by these receptors.…”
Section: Norrin Is the Mammalian Ortholog For Fly Burs And Pbursmentioning
confidence: 99%
“…Activation of Rho/ROCK Signaling by FTY720-P via S1P 2 ROCK signaling (Liu and Wu, 2004;Cheng et al, 2010). Since, in contrast to S1P, FTY720-P did not activate calcium signaling in CHO-S1P 2 cells, we conclude that FTY720-P, at least in CHO-S1P 2 cells, behaved as a biased agonist that selectively activated Ga 12/13 /Rho/ROCK signaling in the absence of the other second messenger release.…”
Section: Discussionmentioning
confidence: 78%
“…The second messenger experiments in this study suggested an absence of cAMP and calcium modulation by FTY720-P through S1P 2 receptors. Furthermore, impedance experiments suggested a selective activation of the Ga 12/13 /Rho/ ROCK pathway by FTY720-P. To confirm the activation of the Ga 12/13 /Rho/ROCK pathway by FTY720-P and S1P in CHO-S1P 2 cells, we employed a Ga 12/13 /Rho/ROCK pathwayspecific reporter gene assay measuring transcriptional activation of firefly luciferase under control of the serum response factor response element (SRF-RE) (Mao et al, 1998;Liu and Wu, 2004;Cheng et al, 2010;Zhang and Xie, 2012). After transient transfection of the CHO-S1P 2 cells with the reporter gene construct, cells were stimulated with different concentrations of FTY720-P, S1P, ponesimod, positive control LPA, or vehicle (Fig.…”
Section: Resultsmentioning
confidence: 99%